2007
DOI: 10.1021/la0700319
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Condensation of DNA Using a Redox-Active Surfactant

Abstract: We report characterization of aqueous solutions of dilute Lambda phage DNA containing the redox-active surfactant (11-ferrocenylundecyl)trimethylammonium bromide (FTMA) as a function of the oxidation state of the FTMA. FTMA undergoes a reversible one-electron oxidation from a reduced state that forms micelles in aqueous solution to an oxidized state (containing the ferrocenium cation) that does not self-associate in solution. This investigation sought to test the hypothesis that FTMA can be used to achieve rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…57, 58 These studies have been driven by the opportunity presented by ferrocenyl surfactants to provide fundamental insights into the interactions between surfactants and macromolecules species, as well as the technological promise of surfactant-macromolecular complexes that are placed under active control. Below, we provide highlights of some recent studies of electrochemical control of complexes formed by electro-active amphiphiles with either semi-synthetic polymers or DNA.…”
Section: Redox-active Surfactants Under Electrochemical Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…57, 58 These studies have been driven by the opportunity presented by ferrocenyl surfactants to provide fundamental insights into the interactions between surfactants and macromolecules species, as well as the technological promise of surfactant-macromolecular complexes that are placed under active control. Below, we provide highlights of some recent studies of electrochemical control of complexes formed by electro-active amphiphiles with either semi-synthetic polymers or DNA.…”
Section: Redox-active Surfactants Under Electrochemical Controlmentioning
confidence: 99%
“…A recent study has explored the extent to which this physical situation can be manipulated through changes in the oxidation state of FTMA in solutions containing DNA. 57 …”
Section: Redox-active Surfactants Under Electrochemical Controlmentioning
confidence: 99%
“…Smith demonstrated that using a chemically degradable dendron framework allows multivalent binding to be switched off, with subsequent loss of affinity for DNA [38]. Lynn and Abbott reported the reversible condensation of DNA using a redox-active surfactant [39]. Compared with the other external stimuli to trigger DNA decompaction and release, light input is considered to be advantageous benefitting from its capability of remote control [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of solving these problems, Tian et al [11] has proposed a novel principle of reversible surfactantenhanced remediation (RSER) based on switchable surfactants. Nowadays, there is a growing attention on switchable surfactants, and it has been found that the aggregation and disruption of the micelles can be reversibly controlled by means of CO 2 /air, electrochemical, photochemical and acid-base changes [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%